Morality of The Prophet Muhammad Rasulullah SAW The People Until The End of Time - Weti Susanti; Sobri Sobri (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2023)
History records that Rasulullah Muhammad SAW is a role model throughout the ages who has noble character who should be emulated in every line of daily life, there is a moral decline, bad behavior from humans, that's why Muslims make examples of the morals of Rasulullah Muhammad SAW. The purpose of this research is to find out the example of the Prophet Muhammad SAW which is a role model until the end of time that can be emulated by humans. The type of research used is literature. The data collection technique was carried out through literature study, namely by collecting several writings from journals and books relating to the morals of Muhammad Rasulullah SAW which should be emulated throughout the ages. Data analysis techniques in this study researchers used content analysis, namely analyzing books, journals and other literature related to research. The results of the research show that: (1) The morals of Rasulullah SAW which should be exemplified until the end of time, including establishing prayer, adorning oneself with noble morals, carrying out instructions for the function of being a wife and mother; (2) How to have morals towards Rasulullah SAW until the end of time, including praying, reviving sunnah, loving the prophet's family, having morals towards Rasulullah SAW is an attitude that humans must do towards Rasulullah SAW as a form of gratitude for his struggle to bring mankind to the right path, including praying, reviving the sunnah and loving the Prophet's family.